Perancangan Tata Letak Fasilitas Menggunakan Metode Konvensional Berbasis 5S dan Metode SLP (Systematic Layout Planning) di PT XYZ - Maulana, Rizki; Windyatri, Hasyrani; Suhendra, Suhendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The design of production facilities plays an important role in the performance of the company because a poor layout can cause inefficient material flow and increase production costs. This research aims to optimize the factory layout to minimize material movement and material handling costs. The methods used include calculating distances and costs in the initial layout, creating an Activity Relationship Chart (ARC), and applying the 5S and Systematic Layout Planning (SLP) methods. The results show that the proposed layout is more efficient, with a reduction in displacement distance from 79.00 meters to 63.79 meters and material handling cost savings from Rp13,108,331.60 to Rp10,709,617.21 per month. As for the SLP method, the results show that the proposed layout is more efficient, with a reduction in displacement distance from 79.00 meters to 62.79 meters and material handling cost savings from Rp 13,108,331.60 to Rp 10,072,708.75 per month.